DIGITALIZATION IMPLEMENTATION IN TRAFFIC POLICE SERVICES: A CASE STUDY OF THE KORLANTAS DIGITAL APPLICATION - Pandli, Gammars Erfi Steve; Pratama, Bima; Nielwaty, Elly (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
Digital transformation within police institutions represents a strategic initiative that not only aligns with technological advancement but also addresses public demands for fast, transparent, and accountable services. One of the concrete manifestations of this transformation is the utilization of digital applications by the Indonesian National Police through the Digital Korlantas platform, which encompasses a variety of services such as motor vehicle registration and identification, issuance and renewal of driving licenses, as well as accident reporting and real-time traffic information. This article examines the implementation of digitalization in traffic police services by positioning the Digital Korlantas application as the primary case study. The writing employs a qualitative approach and literature review, which enables the author to comprehensively analyze theories, concepts, and relevant research findings to build a systematic assessment. The findings indicate that the implementation of digitalization in traffic services has a significant impact on enhancing efficiency, strengthening service integrity, and expanding public access. However, the development of the digital system still faces challenges such as disparities in digital literacy, data security issues, and internal bureaucratic adaptation that requires policy consistency. This study is expected to serve as an academic reference for understanding the dynamics of public service digitalization, particularly in the traffic sector, and to enrich discussions on technology-based police service innovations.